Heterogeneous Spatial Distribution of Transcriptional Activity in Budding Yeast Nuclei - Tokuda, Naoko (Biophys J, 2017)
Recent microscopic and simulation studies have shown that the genome structure fluctuates dynamically in the nuclei of budding yeast Saccharomyces cerevisiae. This genome-wide movement should lead to the fluctuations of individual genes in their territorial regions. This raises an intriguing question of whether the resulting distribution of genes is correlated to their transcriptional activity. An effective method for examining this correlation is to analyze how the spatial distribution of genes and their transcriptional activity are modified by mutation. In this study, we analyzed the modification observed in a budding yeast mutant in which genes necessary for anchoring telomeres to the nuclear envelope, yku70 and esc1, are silenced. Taddei et al. reported that 60 genes are clearly misregulated by this mutation, with 28 and 32 genes downregulated and upregulated, respectively. We calculated the probability density maps of the misregulated genes using a model of dynamical movement of the yeast genome in both wild-type (WT) and yku70 esc1 mutant and showed that the density of downregulated genes is larger near the nucleolus, whereas the density of upregulated genes is larger at the opposite side of the nucleus. By comparing these genes with those highly (top 200 of transcriptome) and lowly (bottom 200) expressed, we showed that the simulated distribution of 28 downregulated (12 out of 32 upregulated) genes has a distinctly larger overlap with the distribution of lowly (highly) expressed genes in the mutant than in the WT. The remaining 20 upregulated genes are localized near the nuclear envelope both in the WT and in the mutant. These results showed that the transcriptional level of genes is affected by their spatial distribution, thus highlighting the importance of the structural regulation in the yeast genome.